A least-significant-bit substitution data hiding scheme by using modulus function and optimal permutation refining. (18th October 2010) - Ho, Yu-An; Feng, Jen-Bang; Lin, Iuon-Chang; Chu, Yen-Ping
Least significant bit (LSB) substitution is one of the most straight and simple technique to hide data hiding in an image. It has been widely used in steganography, watermarking, data compression, and so on. So far, there have been many developments to improve the quality of the embedded images such like genetic algorithm, dynamic programming, modulus functions, etc. To further improve LSB data hiding, an adapted LSB data hiding scheme by using modulus function and optimal permutation search is provided in this paper. The paper presents an LSB-based data hiding scheme by using modulus function and optimal permutation refining. The proposed scheme has higher PSNR values of stego-images in the same capacity that can raise the efficiency of current data hiding schemes and can be used in wide applications.